Using graphic organisers to teach History (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The reality of teaching History in government schools in South Africa is that the subject is many times the “dumping ground” for students not performing well in other subjects. Many learners are not in the subject by choice and are consequently disinterested. Classes are filled to capacity or overfilled - the biggest class I taught had 68 learners. So, naturally, if we do chalk and talk or the textbook marathon, we lose the learners. The challenge is to make History fun, to make it relatable and to get learners involved. It is in this vain that I have used and developed teaching tools that in my view succeed in achieving the above. Evidence of this is that I get a bunch of disinterested learners in Grade 10 and by the time they get to Grade 12, they have been transformed to interested Historians, loving and acing the subject. The results, both in terms of marks and attitude towards the subject, are so good, that my fellow teachers from time to time approach me to ask: “How did you do it? We know the quality of learner you work with, how?” In this article I will share “how” I do it.
Keywords: Make History fun; Teaching tools; Teaching ideas; Methodology; Best practice; Didactics; Graphic organisers; Visual learning